3G Services Adoption among University Students: Diffusion of Innovation Theory - J. W., Ong; Yew-Siang, Poong; Tuan Hock, Ng (2008)
3G services represents an evolution in telecommunication industry. However, 3G services has not received great adoption rule as expected despite of various benefits provided by this service. This study aims to investigate the factors affecting the intention to adopt 3G services among the university students in Malaysia since they expected to be the group with great potential to adopt 3G services. Diffusion of innovation theory is modified and applied in this study to achieve the objective. Results of this study show that perceived compatibility, perceived relative advantage, perceived results demonstrability, perceived trailability, perceived image, and perceived enjoyment are significantly associated with invention to adopt 3G services. Surprisingly, perceived cost of using 3G services is found to be positive but insignificant associated with intention to adopt 3G services. Managerial implications and conclusion have been discussed.